2022
DOI: 10.5194/esd-13-833-2022
|View full text |Cite
|
Sign up to set email alerts
|

Divergent historical GPP trends among state-of-the-art multi-model simulations and satellite-based products

Abstract: Abstract. Understanding historical changes in gross primary productivity (GPP) is essential for better predicting the future global carbon cycle. However, the historical trends of terrestrial GPP, due to the CO2 fertilization effect, climate, and land-use change, remain largely uncertain. Using long-term satellite-based near-infrared radiance of vegetation (NIRv), a proxy for GPP, and multiple GPP datasets derived from satellite-based products, dynamic global vegetation model (DGVM) simulations, and an upscale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Both satellite‐derived vegetation indices and GPP indicated that vegetation exhibited a significant increasing trend before 2000, and in recent years the global vegetation growth rate had weakened due to climate change (Nemani et al., 2003; Pan et al., 2018; Yuan et al., 2019; Zhao & Running, 2010; Zhou et al., 2014). Although the overall trend in GPP has been increasing over the last few decades, there are some differences in the interannual variability (IAV) and estimates obtained using different GPP products (Anav et al., 2015; Yang et al., 2021). Meanwhile, the response of vegetation to climate change is complex, and there is some variation in IAV and long‐term trends of GPP (Ahlström, Raupach, et al., 2015; Cao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both satellite‐derived vegetation indices and GPP indicated that vegetation exhibited a significant increasing trend before 2000, and in recent years the global vegetation growth rate had weakened due to climate change (Nemani et al., 2003; Pan et al., 2018; Yuan et al., 2019; Zhao & Running, 2010; Zhou et al., 2014). Although the overall trend in GPP has been increasing over the last few decades, there are some differences in the interannual variability (IAV) and estimates obtained using different GPP products (Anav et al., 2015; Yang et al., 2021). Meanwhile, the response of vegetation to climate change is complex, and there is some variation in IAV and long‐term trends of GPP (Ahlström, Raupach, et al., 2015; Cao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The GPP NIRv dataset was site-level verified, demonstrating a high correlation coefficient exceeding 0.7 for both monthly and annual variations in GPP. Different from light-use-efficiency (LUE) models, the trends of GPP NIRv are consistent with those from flux sites and process-based models (Yang, Wang, et al, 2022). Notably, the better abilities of GPP NIRv to capture the seasonal and interannual variations of terrestrial GPP are fundamental to detect the drivers of GPP variations and mechanisms of climate forces (Wang et al, 2021).…”
Section: Gross Primary Production (Gpp) Datasetmentioning
confidence: 77%
“…However, in ENF, EBF, DBF, and MF, we observed a weakening E WA-GPP (both positive and negative) for GPP NIRv , which is consistent with previous studies that there is a weakening impact of WA induced by carbon dioxide fertilization effects (Lian et al, 2023;Wang et al, 2020), whereas GPP FLUX and GPP EC-LUE exhibited an increasing E WA-GPP . Considering the better response of NIRv to high vegetation cover areas, we believe that the effect of WA on forests is weakening, which is more plausible, but of course, this needs to be further confirmed by other metrics such as biomass (Wang et al, 2021;Yang, Wang, et al, 2022).…”
Section: Relationships Between Gpp and Wa At Different Time Scalesmentioning
confidence: 95%
“…Given the low sensitivity of these models to environmental scalars, this suggests that dynamic changes in MOD17 modeled GPP are largely a function of changes in canopy extent and vigor, conveyed by changes in fPAR. This feature of LUE models has been an advantage during the EOS era and allowed models like MOD17 to capture trends in the land carbon sink (Figure 5) that are otherwise missed by purely data‐driven approaches like FLUXCOM (Yang et al., 2022). And yet, given the modest improvement in the new MOD17 product compared to C61, it’s also apparent that the accuracy of these global LUE models is strongly tied to the quality of input data sets, in addition to uncertainty in model parameters and model structure.…”
Section: Discussionmentioning
confidence: 99%